The Impact of The Preventive Role of Star Anise on The Toxicity of Benzopyrene Compound in The Liver and Kidney Tissues and Biochemical Parameters in Male Rats - Saleh, Eman Naji; Saeed, Iktefa Abdul Hamid Mohammed; latef, Nedhal ibrahim (South Eastern European Journal of Public Health, 2024)
Objective: This study, conducted at the University of Anbar's College of Pure Science, evaluated the protective effects of star anise against benzopyrene (B[a]P)-induced liver and kidney damage in 30 male white Swiss rats (Sprague Dawley), aged 3-4 months and weighing between 170-210 g. Materials and methods: The rats were divided into six groups: Control (G1), B[a]P (G2), Star Anise 125 mg/kg bw (G3), Star Anise 120 mg/kg bw + B[a]P (G4), Star Anise 125 mg/kg bw + B[a]P (G5), and Star Anise 130 mg/kg bw + B[a]P (G6). Results:Biochemical analyses showed that B[a]P exposure significantly elevated liver enzymes (ALP, AST, ALT, GGT) and kidney markers (uric acid, creatinine), indicating hepatic and renal damage. Treatment with star anise, especially 130 mg/kg bw significantly reversed these elevated levels because it protected against the injury. Histopathology showed that the liver and kidney were severely damaged in the B[a]P group and in the star-anise-treated group, normal tissue architecture was well preserved only in high doses of star anise treatment. Conclusion:These outcomes suggest the use of star anise as a hepatoprotective as well as a nephroprotective agent, and this needs to be further strengthened by understanding its mechanisms and long-term effectiveness.